2022
DOI: 10.21037/jtd-22-86
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of pyroptosis-related factors in lung adenocarcinoma

Abstract: Background: Numerous studies have revealed that the abnormal expression of pyroptosis-related genes is closely related to the prognosis of lung adenocarcinoma (LUAD); however, a comprehensive analysis has yet to be conducted. This study aimed to reveal the influence of pyroptosis-related genes on the prognosis of LUAD and establish a prognostic model based on those genes, in order to evaluate the prognosis of LUAD. Methods:The data of tumor and normal samples were downloaded from The Cancer Genome Atlas (TCGA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Tubulin plays a crucial role in tumorigenesis and has shown potential prognostic value in various solid tumours [ 36 , 37 ]. Recent studies have demonstrated that TUBB6 (tubulin beta 6 class V) promotes the growth of cancer tissue in multiple solid tumours and serves as an important prognostic factor [ [38] , [39] , [40] ]. Our findings further support this concept.…”
Section: Discussionmentioning
confidence: 99%
“…Tubulin plays a crucial role in tumorigenesis and has shown potential prognostic value in various solid tumours [ 36 , 37 ]. Recent studies have demonstrated that TUBB6 (tubulin beta 6 class V) promotes the growth of cancer tissue in multiple solid tumours and serves as an important prognostic factor [ [38] , [39] , [40] ]. Our findings further support this concept.…”
Section: Discussionmentioning
confidence: 99%
“…Calibration curves were also plotted for 1-, 2-, and 3-year overall survival rates (Figure 7B). To test the effect of our model, patients were divided into high-risk and low-risk groups according to the median value of the risk score in the training and validation sets Lin et al, 2022). The risk curve (Supplementary Figure S2A) and the survival distribution figure (Supplementary Figure S2B) were plotted for the training set.…”
Section: Evaluation and Validation Of Prognostic Modelsmentioning
confidence: 99%
“…At present, with the development of microarray and sequencing technology, genetic testing technology is becoming increasingly common. Based on bioinformatics approach, one study explored a prognostic model for lung adenocarcinoma from the perspective of pyroptosis-related factors (Lin et al, 2022), and one study explored a prognostic model for IPF from the perspective of immune-related chromatin regulatory genes (Li et al, 2022). However, translating the clinical and prognostic value of EMT-related genes to IPF requires extensive research.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the complex tumor microenvironment in GBM, the connections between 22 immune cells activity and the prognostic signature were investigated using the celltype identi cation by estimating relative subsets of RNA transcripts (CIBERSORT) analysis [23]. Moreover, the immune score, ESTIMATE score and stromal score were calculated by the Estimation of Stromal and Immune cells in Malignant Tumor tissues using Expression data (ESTIMATE) algorithm [24].…”
Section: Immune In Ltration In Tme Of Gbmmentioning
confidence: 99%